2014
DOI: 10.1051/matecconf/20141401002
|View full text |Cite
|
Sign up to set email alerts
|

Compositional effect on TCP phase formation in Ru-containing Ni-based single crystal superalloys

Abstract: Abstract. Microstructural instability involving the formation of topologically close-packed (TCP) phases is restricted during the alloy development of Ni-based single crystal superalloys. In this study, the effects of alloying elements including Co, Cr, Mo and Ru on the formation of different TCP phases were investigated in a series of single crystal superalloys. Experimental results showed that more additions of Cr and Mo promoted the TCP phase formation, while Co and Ru played a positive role in improving mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…During dendritic solidification of Ni-based superalloys, the process of solute enrichment leads to variation in partition coefficients of refractory elements. When these solute rich regions are exposed to higher temperatures for longer durations, which happens during ageing or annealing or--as observed in this study--reheating during SEBM process, TCP phases are formed [120,121,123,124,[275][276][277][278]. It is believed that the presence of Laves based TCP phases in as-built specimens is the outcome of the inherent non-equilibrium nature of solidification in AM processes.…”
Section: Meso-scale Microstructure and Cracking In As-built Samplessupporting
confidence: 51%
See 2 more Smart Citations
“…During dendritic solidification of Ni-based superalloys, the process of solute enrichment leads to variation in partition coefficients of refractory elements. When these solute rich regions are exposed to higher temperatures for longer durations, which happens during ageing or annealing or--as observed in this study--reheating during SEBM process, TCP phases are formed [120,121,123,124,[275][276][277][278]. It is believed that the presence of Laves based TCP phases in as-built specimens is the outcome of the inherent non-equilibrium nature of solidification in AM processes.…”
Section: Meso-scale Microstructure and Cracking In As-built Samplessupporting
confidence: 51%
“…Based on these reflections, it can be inferred that the secondary precipitates present at GBs are C14 Laves phase that has an HCP structure. Several previous studies on Ni-based superalloys have also reported the formation of these phases, and have referred to them as TCP precipitates [120,121,123,124,[275][276][277][278]. These precipitates are generally irregular in shape and form when the alloy is aged at high temperatures for extended periods [278].…”
Section: Meso-scale Microstructure and Cracking In As-built Samplesmentioning
confidence: 98%
See 1 more Smart Citation
“…The precipitation kinetics of Re–Ru–Ni-rich phase is not uniform in the whole sample. Noticeable differences in the evolution of the precipitates were identified for the dendrite core, arm and interdendritic regions, Figure 6(a,b), while in most of the papers [21,22,30] only dendrite cores, as the most critical areas with respect to TCP or HCP phase formation, were taken into account. However, in this study it was shown that even small changes in chemical composition can strongly affect the formation of Re–Ru–Ni-rich precipitates.…”
Section: Discussionmentioning
confidence: 99%